Originally Posted by

**Hikaru** Heya! =]

Right now I'm down to the last question, but my brain isn't really helping me finish it off. :P

The answer in the book says Y= 1, but I keep on getting Y=2.09

So could you guys help me figure out how to solve it? =[

This is the question:

-2 -3y = x

3x -2y = -17

Find X and find Y.

(Once I find one out, I can easily complete the other. :D)

And this is how I carry it out:

-2y + 3 (-2 -3y) = -17

-2y -6 = -17 Mr F says: Wrong. It's -2y - 6 - 9y = -17. When you expanded the 3 (-2 - 3y) term, you forgot to multiply the 3 with the -3y .....!!

-11y -6 = -17 Mr F says: Oh .... This is actually correct. So you didn't make the above mistake. You just didn't write it in.

-11y = -23 Mr F says: OK, this is wrong. When you add the 6 to both sides, -17 + 6 = -11, NOT -23. So it should be -11y = -11. It clearly follows that y = 1.

11y/11 = -23/11

Therefore y = 2.09?

But that's not right. =[

Thanks in advance!